Research of transport specialis competences in Lithuania and Slovénia - Ledauskaité, Kristina; Kovač, Janja (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Competitiveness is closely related to business management, operational efficiency, and new approaches to the management of search. One of the most important and intractable problems of the transport companies remain effective management of the problem, covering a wide range of issues. This is a rational organizational structures, which are not always meeting the company's strategic objectives, set up; advanced management methods, which often are only the failed experience fitting of foreign countries without the necessary adaptation; management of democratization; the staff, especially top-level managers, the potential and environmental non-compliance, the lack of ability to understand the overall economic development trends, make informed decisions, to ensure the company's competitive capacity (Gal J. 2008). In order shape the competitive enterprises realistically, it is necessary to use consistently all opportunities to change the heads of management. This will help not only the traditional methods of enhancing their competence, but the new management philosophy and the installation of plants. The faster and clearer our transport business leaders understand that the company's competitiveness is not only the subject they are and all the staff, the greater the opportunity to become a fully fledged market economy. Recently, rapid changes during the period of not less important is the manager and the social competence, i.e., the effectiveness of social behavior, the ability to adapt to the dynamically changing environment and to take corresponding changes in the decisions. Social competence criteria - this consist of the whole social skills (which includes both verbal and non verbal communication skills) the ability to form interpersonal relationships, be well-liked in group, the ability to achieve the goals. Management has the competence to disclose not only the knowledge and experience, but personal qualities / characteristics as well. Personal competence - the self-assessment of skills and personal characteristics of the combination (of humor to work, motivation, development and the desire to work, and beyond), which is not the level of knowledge, but the employee's personal characteristics (personal qualities, character and mental qualities, behavioral targeting). Therefore, a lot of career success depends on how the graduate is able to evaluate a particular enterprise or workplace evolving situation and adopt a self-optimal management decisions. Of course, professional, capable practical situations to make the right transportation management solutions, development inevitably must rely on general subjects; the learning is based on certain definitions and classification of knowledge systems. In this article will be submitted to the Lithuanian and Slovenian transport expertise in the study results.